Hepatitis C virus infection: Epidemiology in Egypt, Pathophysiology and DAAs-based therapy - Heba Elbadawy; Sara Wahdan; Ebtehal El-Demerdash (Ain Shams University, 2021)
Hepatitis C virus (HCV) was first identified in 1989. The situation in Egypt is really dire. The prevalence of HCV genotype 4 (GT-4) is 14.7%. About 10% of the middle-aged population (ages 15 to 59) is infected with HCV. As a result, the Hepatitis C virus is considered extremely contagious. The introduction of the directly acting antiviral medications (DAAs), sofosbuvir or simeprevir, in GT-4 patients with PEGylated interferon (PEG-IFN) and ribavirin (RBV) in a 12-week regimen substantially increased sustained virological response (SVR) rates for HCV GT-4 in 2014. Daclatasvir (DCV) is the first DAA identified in the family of HCV NS5A inhibitors with antiviral activity against a variety of HCV genotypes. It is well tolerated and safe, with a low risk of drug-drug interactions and resistance. Many investigations have discovered a rapid initial viral decline followed by a gradual decline in viral RNA, demonstrating DCV's inhibitory effect on viral reproduction, assembly, and secretion. DCV is a CYP3A4 substrate as well as a substrate for P-glycoprotein (P-gp), the most common drug efflux transporter, which are both expressed in hepatocytes and enterocytes, however it is not a BCRP substrate (Breast Cancer Resistence Protein). Concomitant treatment of DCV with other medications targeting CYP3A4 or P glycoprotein may change its pharmacokinetic characteristics.